Port Jews : Jewish Communities in Cosmopolitan Maritime Trading Centres, 1550-1950. - Cesarani, David (Taylor and Francis, 2014)
The history of Jews in cosmopolitan maritime trading centres is a field of research that is reshaping our understanding of how Jews entered the modern world. These studies show that the utility of Jewish merchants in an era of European expansion was vital to their acculturation and assimilation.